Implementation Of The Deep Independent Curriculum Learning Education Religion Islam - Fahmi, Ryan; Heryadi, Heryadi; Azmaliyah, Azmaliyah (-, 2024)
The aim of this research is to explore the implementation of the independent curriculum in Islamic religious education learning in Madrasas. Data collection was carried out by means of observations, interviews and documentation. The data analysis technique used is an interactive analysis technique which includes data collection, data reduction, data presentation, then drawing conclusions. The results of this research are the implementation of an independent learning curriculum in Islamic religious education learning in accordance with the policies of the Indonesian Ministry of Education and Culture, so that students are more enthusiastic about participating in the learning process with better learning creativity.